True or False Strategy Learning: Mediators Increase Students' Active Role in Class - Sudjoko S; Fathor Rozi; Zumrotus Sholehah; Wardatul Jannah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This research aimed to determine the implementation and success of true or false learning strategies which mediate students' active role in learning. This research used a qualitative approach with the type of Classroom Action Research. The subjects of this research were class B students (18 students). Data collection techniques used observation, interviews and documentation for each cycle process. Validate research data by means of technical triangulation. The results showed that students' active role scores have increased in each cycle action. It can be seen that the score for the active role of class B students (classically) in learning obtained an average of 50 which increased to 64 in cycle I and was followed by a significant increase in cycle II to 89. Achievements and improvements obtained after being given learning strategy actions were true or false makes learning more meaningful, fun, and brings out student activity. Student involvement plays an active role in finding answers to problems through a process of collaboration, thinking and discussion. This research contributed to prioritizing the development of student-centered learning that is effective, collaborative and productive.